1988
DOI: 10.1051/jphys:01988004905086100
|View full text |Cite
|
Sign up to set email alerts
|

Solutions of polydiacetylenes in good and poor solvents : a light and neutron scattering study

Abstract: To cite this version:M. Rawiso, J.P. Aime, J.L. Fave moléculaire élevée. On n'a pas observé de véritables solutions rouges de bâtonnets isolés, même à des concentrations aussi faibles que 0,5 x 10-3 g 1-1 de P-4BCMU de grande masse moléculaire (Mw = 1,67 x 106 gmole-1) ou 0,5 gl-1 de P-4BCMU de petite masse moléculaire (Mw = 4,32 x 104 g mole-1). Ceci suggère que dans toutes les expériences sur les solutions bleues ou rouges de P-3BCMU et P-4BCMU on n'observe que des agrégats. Cependant, la question reste ouve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 42 publications
6
67
2
Order By: Relevance
“…[16,29,42] Neutron scattering studies have shown that in solution the yellow, disordered, polymer is best described as a worm-like chain. [43] The optical and Raman spectra of the blue-phase polymer are similar to those of the as polymerised, crystalline polymer, hence, it follows that the polymer structure is also similar in both situations. [16,42,44,45] The transition between disordered and ordered forms has been considered to be due to either the full extension of individual polymer chains or extension associated with self-collapse of individual polymer chains and aggregation.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…[16,29,42] Neutron scattering studies have shown that in solution the yellow, disordered, polymer is best described as a worm-like chain. [43] The optical and Raman spectra of the blue-phase polymer are similar to those of the as polymerised, crystalline polymer, hence, it follows that the polymer structure is also similar in both situations. [16,42,44,45] The transition between disordered and ordered forms has been considered to be due to either the full extension of individual polymer chains or extension associated with self-collapse of individual polymer chains and aggregation.…”
Section: Introductionmentioning
confidence: 72%
“…Tetrahydrofuran and DMF are good solvents for the nBCMUs. [43,53] Tetrahydrofuran has a similar boiling point to chloroform and, therefore, was not investigated as a solvent for 9EU. In the initial study, DMF was not heated close to its boiling point.…”
Section: Polymer Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intriguing effect has been extensively studied and has led to the development of various thermochromic polythiophene [4,5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], polysilane [30][31][32][33][34][35][36][37][38][39][40][41], and polydiacetylene [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] derivatives (Figure 2.1). As an example of thermochromism reported for some neutral conjugated polymers, Figure 2.2 shows the temperature-dependent UV-vis spectrum of sodium poly[2-(4-methyl-3-thienyloxy)ethanesulfonate] in...…”
Section: Thermochromism and Structural Aspectsmentioning
confidence: 99%
“…In order to obtain absolute measurements, SANS experiments were carried out by Wegner et al [24]. P3BCMU and P4BCMU samples with comparatively low MW (~43200) and reasonable polydispersity were used in the study.…”
Section: Pda Chromismmentioning
confidence: 99%